2015
DOI: 10.15390/eb.2015.2822
|View full text |Cite
|
Sign up to set email alerts
|

Student-Centred Learning (SCL) in Schools in North Cyprus: Teachers' Opinions and ProblemsThe Implementation of Student-Centred Instructional Strategies in Schools in North Cyprus

Abstract: ÖzAnahtar Kelimeler GirişSon zamanlarda, okullarda yapılan öğretimin niteliğini artırmak amacıyla dünyanın her yerinde eğitim reformları ve eğitimi geliştirme çalışmaları yapılmaktadır. Günümüzde, öğrencilerin iletişim kurma, etkili düşünme ve usavurma, yargıda bulunma, karmaşık sorunları çözme ve işbirliği yaparak çalışma becerilerini kazanmalarını sağlayacak biçimde öğretimin geliştirilmesi ve uygulanması önemtaşımaktadır (Gijbels, Van de Watering, Dochy ve Van den Bossche, 2006). Öğretimin öğretmenin tekel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 32 publications
(44 reference statements)
0
5
0
Order By: Relevance
“…In addition, 39.1% were not in favour of consulting students to provide their evaluation of methods used. These findings appear to score the college low on these basic elements of SCL process which requires the student to play active role at every stage of the teaching and learning process [4].…”
Section: Instructional Strategiesmentioning
confidence: 86%
See 4 more Smart Citations
“…In addition, 39.1% were not in favour of consulting students to provide their evaluation of methods used. These findings appear to score the college low on these basic elements of SCL process which requires the student to play active role at every stage of the teaching and learning process [4].…”
Section: Instructional Strategiesmentioning
confidence: 86%
“…This study revealed that instructional strategy correlated very well with assessment (r = 0.721), role of lecturers (r =.570), and role of students (r =.710). The outcome was not unexpected as instructional strategy largely depend on the role lecturers and students agree on and are expected to play in the instructional process, including the choice of the most suitable mode of assessment [4]. Again, assessment was found to highly correlate with role of lecturers (r =.807), role of students (p =.806), learning environment (r =.659) and overall estimated SCL (r =.937) components.…”
Section: Comparison Of the 8 Scl Assessment Componentsmentioning
confidence: 89%
See 3 more Smart Citations